Examining the effects of child care subsidy eligibility on children's child care experiences - Caronongan, Pia (Ann Arbor Michigan ProQuest LLC, 2009)
Child care subsidy programs, such as the Child Care and Development Fund (CCDF), were designed to help defray the child care expenses of low-income families and support parents' labor force participation. However, the increasing evidence linking child care experiences to children's developmental outcomes has also led to questions about whether subsidies can increase the use of certain types of child care arrangements that have been shown to have positive effects on children. This study examines the causal effect of CCDF subsidy eligibility status on children's subsequent care arrangements, using a regression discontinuity design (RD). States provide subsidies to families whose incomes fall below a particular income threshold. I take advantage of this rationing mechanism to compare the child care participation of children whose families have very similar incomes but whose eligibility statuses differ by virtue of their state threshold. Using core and topical module data from the 2001 and 2004 Survey of Income and Program Participation, I find that subsidy eligibility increased the probability of participating in home-based arrangements for the average child by 17 percentage points. Further, eligible children with at least one home-based arrangement spent over 4 hours more per week in home-based settings, on average, compared with their ineligible counterparts. The effect of subsidy eligibility appears to be largest for families with more than one young child between the ages of 0 to 5, and families headed by a single parent. I find no evidence that subsidy eligibility increases the use of center-based care.
Thesis (Ed. D.)--Harvard Graduate School of Education, 2009.
Keywords: Early childhood education -- United States; Children with social disabilities -- Education (Elementary) -- United States; Poor children -- Education (Early childhood) -- United States